Carers' quality of life and experiences of adult social care support in England. (12th December 2013) - Rand, Stacey; Malley, Juliette
Abstract Informal carers make a vital contribution to the well‐being of the people they care for or look after. Against the policy background in England, the purpose of this study was to explore the views of carers who are in contact with adult social care support services. A qualitative study with 31 carers, who were recruited via local authorities and carers' organisations, was conducted between April and July 2012 to collect data on carers' experiences and perceptions of their quality of life (QoL) with and without adult social care and support for themselves or the person they look after. Through framework analysis, three key themes were identified: (i) definitions of social care services 'for' the carer or 'for' care recipient and social care outcomes; (ii) carers' access to social care services; and (iii) the meaning and value of informal care. We find that carers' QoL is affected by social care support directed at carers and support directed at those they care for, as well as access to services, the experience of stigma in communities, and in how individual needs and preferences are considered when making decisions about care. While there is much to welcome in the direction of policy in England, this study has shown that there are some gaps in thinking around these areas that will need to be addressed if the lives of carers are to be improved.